Pengaruh Motivasi Belajar Terhadap Mata Kuliah Metodologi Penulisan Ilmiah - Wilhelmina W. Pingge; Yehezkiel F. Umbu; Frederikus B. Rina; Yermias Bili (Pusat Riset dan Inovasi Nasional, 2024)
Sumba Kitchen offers a variety of food menus. Not just local specialty food. There is also a menu of Indonesian food such as meatballs, rawon, fried noodles and processed sea fish. There are also western dishes such as pizza, burgers and spaghetti. So for those of you who find it difficult or afraid to enjoy new dishes, you can choose Indonesian and Western menus which are already familiar to your tongue, this could be a solution. Another interesting thing apart from opening a restaurant and cafe, the owner of Dapur Sumba also opened a bakery called Galaxy Bakeries. So for tourists who want to buy snacks to snack on while traveling or who intend to buy souvenirs for people at home, you can buy them here. Dapur Sumba also provides HR (Human Resources) who are qualified to provide services in restaurants, cafes and bakeries. . The human resources prepared by the owner of Dapur Sumba are in the form of (reliability, responsiveness and empathy). This research aims to analyze the influence of service quality on customer satisfaction. There are three hypotheses developed in this research, namely: 1) Customer quality has a positive effect on customer satisfaction. Data collection method is through distributing questionnaires to respondents directly. The respondents in this research were Sumba Kitchen customers. The number of questionnaires distributed was 98. The test technique used uses a validity test and a reliability test. Testing the first and second hypotheses uses a simple linear regression test. The research results show that service quality has a positive and significant effect on customer satisfaction